(untitled) (Pursuits: A Journal of English Studies, 2025)
The article explores the aesthetics of Dalit literature and its foundation and characteristics connecting with socio-political significance, emphasizing its role in the Dalit movement and its potentiality for social transformation. Through qualitative methods and an exploratory-analytical approach, the study draws on interviews with writers on Dalit issues and politicians to examine the themes, motifs, and challenges of Dalit literature; and, its connection to broader Dalit struggles. The analysis explores the unique aesthetics of Dalit literature, characterized by its realistic depiction of Dalit experiences, its revolutionary spirit, and its commitment to challenging caste-based discrimination and oppression. The scholars and interviewees highlight that Dalit literature not only reflects the pain, suffering, and resilience of Dalits but also envisions a future free from casteism, serving as both a mirror and a roadmap for social change. Moreover, the study underscores the interdependence of Dalit literature and the Dalit movement, positioning literature as a cultural and political tool to raise awareness, mobilize action, and advocate for rights, equality, and justice. By merging artistic expression with ideological clarity, Dalit literature critiques the caste system while offering a vision for an equitable, caste-free society.